2011
DOI: 10.1007/s00296-011-2043-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of suicidal ideation in SLE inpatients: Chinese experience

Abstract: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease that affects multiple organs. Because of double damages of body and mind, SLE patients are in a potential risk of suicide. Many factors may contribute to the occurrence of suicide in SLE: socioeconomic factors, medical factors, mental health, family support and coping style. This study aims to investigate the prevalence and correlates of suicidal ideation in SLE inpatients in China in order to determine whether they had risk of suicide, and if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 19 publications
4
52
2
7
Order By: Relevance
“…67 These problems manifest in the inconsistency with which suicidal phenomena have been defined and measured in included studies. In some, for example, suicidal ideation is defined as 'thoughts of killing oneself' 43 while others define the same concept as 'a spectrum of self-destructive thoughts or ideas'. 39 Some studies focus on very particular kinds of non-fatal SIB (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…67 These problems manifest in the inconsistency with which suicidal phenomena have been defined and measured in included studies. In some, for example, suicidal ideation is defined as 'thoughts of killing oneself' 43 while others define the same concept as 'a spectrum of self-destructive thoughts or ideas'. 39 Some studies focus on very particular kinds of non-fatal SIB (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…All three studies focusing on completed suicide used bivariate analysis only, reporting one 51 positive, one 38 null, and one 62 unclear association. Amongst the four 32,43,50,53 studies on non-fatal SIB, one 43 showed positive and one 32 a null association using bivariate analyses. When multivariate analyses were performed, the results were similar with two studies reporting positive associations between non-fatal SIB and economic or financial problems.…”
Section: Economic or Financial Problemsmentioning
confidence: 93%
See 2 more Smart Citations
“…In adults with SLE, suicidal ideation is common in up to one-third of patients with and without NPSLE, and is associated with higher disease activity, increased depression and anxiety severity and previous suicide attempts (Karassa et al, 2003;Mok et al, 2014;Xie et al, 2012).…”
Section: Depression-like Symptoms In Systemic Lupus Erythematosusmentioning
confidence: 99%